Prolactin at moderately increased levels confers a neuroprotective effect in non-secreting pituitary macroadenomas - David A. Paul; Alejandra Rodrigue; Nicholas Contento; Sam Haber; Ricky Hoang; Redi Rahmani; Adnan Hirad; Ismat Shafiq; Zoë Williams; G. Edward Vates (PLoS ONE, 2022)
Context Prolactin, a hormone synthesized by the anterior pituitary gland demonstrates promise as a neuroprotective agent, however, its role in humans and in vivo during injury is not fully understood. Objective To investigate whether elevated levels of prolactin attenuate injury to the retinal nerve fiber layer (RNFL) following compression of the optic chiasm in patients with a prolactin secreting pituitary macroadenoma (i.e., prolactinoma). Design setting and participants A retrospective cross-sectional study of all pituitary macroadenoma patients treated at a single institution between 2009 and 2019. Main outcome measure(s) Primary outcome measures included RNFL thickness, mean deviation, and prolactin levels for both prolactin-secreting and non-secreting pituitary macroadenoma patients. Results Sixty-six patients met inclusion criteria for this study (14 prolactin-secreting and 52 non-secreting macroadenoma patients). Of 52 non-secreting macroadenoma patients, 12 had moderate elevation of prolactin secondary to stalk effect. Patients with moderate elevation in prolactin demonstrated increased RNFL thickness compared to patients with normal prolactin levels (p < 0.01). Additionally, a significant positive relation between increasing levels of prolactin and RNFL thickness was identified in patients with moderate prolactin elevation (R = 0.51, p-value = 0.035). No significant difference was identified between prolactinoma patients and those with normal prolactin levels. Conclusions Moderately increased serum prolactin is associated with increased RNFL thickness when compared to controls. These associations are lost when serum prolactin is < 30 ng/ml or elevated in prolactinomas. This suggests a neuroprotective effect of prolactin at moderately increased levels in preserving retinal function during optic chiasm compression.